Traffic accident criminal act resulting in loss of life at Medan city police office (study of decision number 2698/pid.sus/2018/pn lbp) - Suratman, Suratman; Harahap, Herlina Hanum (Journal of Law Science, 2024)
Traffic accidents are one of the serious problems that threaten the safety of people around the world, including in the jurisdiction of the Medan Police. Every year, thousands of lives are lost and tens of thousands of people are injured due to road accidents. The type of research used in this study is juridical-empirical. Juridical-empirical research is legal research regarding the implementation or enforcement of normative legal provisions directly in every specific legal event that occurs in society. Data collection methods are techniques or methods that can be used by researchers to collect data. Techniques in designating an abstract word that is not manifested in objects, but can only be seen in its use through: questionnaires, interviews, observations, exams (tests), documentation, and others. The crime of "due to negligence causing death" as referred to in the Criminal Code concerning "causing death or injury due to negligence" Article 359 of the Criminal Code, the punishment is increased if the crime is committed in a position or job. Based on the above considerations, the judge sentenced the defendant Yanto to 7 months in prison, minus the period of detention that has been served. In addition, the judge ordered the return of evidence to the rightful party. In this case, the evidence returned included the Fuso Dump Truck and other vehicles involved in the accident. The judge also determined the court costs to be paid by the defendant as part of the sanction. A comprehensive solution to dealing with criminal acts of traffic accidents resulting in loss of life requires a comprehensive and integrative approach. So in this closing chapter, a conclusion can be drawn. Based on the analysis, this regulation already covers important aspects such as speeding violations, drunk driving, and vehicle conditions. The judge's considerations in Decision Number 2698 / Pid.Sus / 2018 / PN Lbp show an emphasis on the aspect of proving guilt and imposing penalties that are in accordance with the level of violation and the impact of the accident. The solution to overcoming criminal acts of traffic accidents resulting in loss of life involves several strategic steps. First, stricter law enforcement and increased public awareness of driving safety must be strengthened to prevent violations that have the potential to cause accidents.